2019
DOI: 10.3389/fpsyg.2019.01549
|View full text |Cite
|
Sign up to set email alerts
|

Can Mindfulness-Based Training Improve Positive Emotion and Cognitive Ability in Chinese Non-clinical Population? A Pilot Study

Abstract: Objective Based on eastern philosophy, mindfulness is becoming popular for human being’s mental health and well-being in western countries. In this study, we proposed to explore the effectiveness and potential pathway of mindfulness-based training (MBT) on Chinese Non-clinical higher education students’ cognition and emotion. Methods A paired control design was used. 48 higher education students (24 in MBT group, 24 in control group) were recruited in the study. The MBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Recently, Lorca et al (2019) suggested that a single-session mindfulness practice using a meditation recording reduced both subjective and objective anxiety in patients undergoing a PET/ CT study. With the support of a previous study, mindfulness interventions can significantly improve participants' positive emotions (Keng et al, 2011), reduce the self-reported level of anxiety and depression (Hoge et al, 2013;Würtzen et al, 2013;Liu et al, 2019;Zhu et al, 2019;Buckner et al, 2020), and even adjust heart rate (Lorca et al, 2019). Our results are consistent with the conclusion that mindfulness interventions can adjust a patient's mood and may have clinical implications for people in quarantine to reduce psychological stress.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recently, Lorca et al (2019) suggested that a single-session mindfulness practice using a meditation recording reduced both subjective and objective anxiety in patients undergoing a PET/ CT study. With the support of a previous study, mindfulness interventions can significantly improve participants' positive emotions (Keng et al, 2011), reduce the self-reported level of anxiety and depression (Hoge et al, 2013;Würtzen et al, 2013;Liu et al, 2019;Zhu et al, 2019;Buckner et al, 2020), and even adjust heart rate (Lorca et al, 2019). Our results are consistent with the conclusion that mindfulness interventions can adjust a patient's mood and may have clinical implications for people in quarantine to reduce psychological stress.…”
Section: Discussionsupporting
confidence: 88%
“…In the last few decades, mindfulness-related interventions have been applied extensively both in China and abroad, especially in clinical settings (Hoge et al, 2013;Würtzen et al, 2013;Liu et al, 2019;Buckner et al, 2020); however, they also affect the non-clinical population (Arch and Craske, 2006;Zhu et al, 2019). Recently, Lorca et al (2019) suggested that a single-session mindfulness practice using a meditation recording reduced both subjective and objective anxiety in patients undergoing a PET/ CT study.…”
Section: Discussionmentioning
confidence: 99%
“… 32 One study supported the efficiency of MBT on cognition and emotion of Chinese non-clinical higher education students. 33 Another empirical study suggested that perceived stress was positively associated with anxiety/depression, self-compassion was negatively associated with perceived stress, and self-compassion had no significant correlation with anxiety/depression. 34 Admittedly, based on cognitive behavioral therapy (CBT) principles and mindfulness-based interventions (MBIs), the strongest evidence for effectiveness in reducing stress in the workplace is for stress-management courses.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore perhaps unsurprising that research examining the effect of MBIs on cognitive control have yielded mixed results. Several studies reported no change in behavioral performance on the Stroop task after MBI training relative to active (Jensen, Vangkilde, Frokjaer, & Hasselbalch, 2012;Josefsson, Lindwall, & Broberg, 2014) and waitlist controls (Anderson et al, 2007;Zhu, Xue, Montuclard, Jiang, Weng, & Chen, 2019). Similar null findings have been reported for flanker performance on the ANT-neither MBSR nor a 14session college mindfulness seminar improved performance relative to controls (Jha, Krompinger, & Baime, 2007;Tang, Broderick, Bono, Dvorakova, & Braver, 2020).…”
Section: Mindfulness Trainingmentioning
confidence: 99%